Consumer Response to Boil Water Notifications During Winter Storm Uri. Issue 5 (31st May 2022) - Day, Ashleigh M.; Islam, Khairul; O'Shay, Sydney; Taylor, Kristin; McElmurry, Shawn P.; Seeger, Matthew W.
Key Takeaways: Boil water notifications (BWNs) issued during 2021's Winter Storm Uri were typically followed, especially in households with children present and those with higher income. Cascading failure of interconnected systems (such as power and drinking water) inhibited some individuals from being able to follow boil water guidance. Of the people who boiled their water following BWNs, more than 92% reported boiling it for 2 minutes or more.